2001
DOI: 10.1177/003172170108300116
|View full text |Cite
|
Sign up to set email alerts
|

The District Role in Instructional Improvement

Abstract: Are changing conditions affecting the capacity of districts to provide focus, to coordinate support, and to scale up successful reforms? From a study of the roles played by central office staff members in shaping and supporting instructional reforms in three large urban districts, the authors derive an answer. Comments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 0 publications
2
105
0
1
Order By: Relevance
“…Second, evidence is used to back existing opinions or decisions, to legitimise them or to complete them. Third, evidence is used for setting up programmes or measures (Corcoran et al, 2001;Marsh, 2006). Considering its significance for building up political support, some authors conclude that evidence does not have a direct, independent effect on decision making, but rather that it is mediated by public opinion (Englert et al, 1977;Kennedy, 1982a).…”
Section: Insights From the European And American Areasmentioning
confidence: 99%
“…Second, evidence is used to back existing opinions or decisions, to legitimise them or to complete them. Third, evidence is used for setting up programmes or measures (Corcoran et al, 2001;Marsh, 2006). Considering its significance for building up political support, some authors conclude that evidence does not have a direct, independent effect on decision making, but rather that it is mediated by public opinion (Englert et al, 1977;Kennedy, 1982a).…”
Section: Insights From the European And American Areasmentioning
confidence: 99%
“…However, as Corcoran (2001) pointed out, school staff members often paid lip service to the use of research in classrooms and were more interested in designs that drew on research about practices. It is therefore significant to discuss the characteristics of effective PD viewed and suggested by researchers in the world and use them as starting points in planning and implementing effective professional development programs for language teachers with consideration of the contextual factors of Vietnam.…”
Section: Suggestions For Effective Pd In the Vietnamese Contextmentioning
confidence: 99%
“…For example, studies of central office administrators found that they most often considered budgetary, political, and administrative issues when framing policy discussions, suggesting that the practicalities of district governance, rather than evidence, set parameters for decision making (Burkhardt & Schoenfeld, 2003;Fusarelli, 2008;Lagemann, 2002). District administrators appear to weigh multiple forms of information simultaneously when making decisions rather than to rely on one or two instrumental student data points or research studies (Corcoran, Fuhrman, & Belcher, 2001;Kennedy, 1982).…”
Section: Introductionmentioning
confidence: 99%